Peningkatan pengetahuan programmer prolanis terkait diabetes self-management selama puasa ramadan - Sugiharto Sugiharto; Sulastri Sulastri; Wiwiek Natalya (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Ramadan fasting could provide numerous benefits for the body. However, it could also cause acute complications for people with diabetes. Therefore, consultation before fasting is crucial. Healthcare workers must have sufficient knowledge to provide accurate, evidence-based information. Purpose: To increase the knowledge of non-communicable disease (NCD) programmers and PROLANIS. Method: This community service program involved all non-communicable disease (NCD) and PROLANIS programmers. Education regarding diabetes and Ramadan was provided in accordance with International Diabetes Federation guidelines, as well as a fasting risk assessment using the